2011
DOI: 10.1152/jn.00887.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reticulospinal neurons controlling forward and backward swimming in the lamprey

Abstract: Zelenin PV. Reticulospinal neurons controlling forward and backward swimming in the lamprey. J Neurophysiol 105: 1361-1371, 2011. First published January, 19, 2011 doi:10.1152 doi:10. /jn.00887.2010brates are capable of two forms of locomotion, forward and backward, strongly differing in the patterns of motor coordination. Basic mechanisms generating these patterns are located in the spinal cord; they are activated and regulated by supraspinal commands. In the lamprey, these commands are transmitted by reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Similar control schemes are seen in the lamprey (Buchanan and Cohen, 1982; McClellan and Grillner, 1984; Deliagina et al, 2002). Some reticulospinal neurons, for example, are dedicated to forward or backward locomotion (Zelenin, 2005), although the majority participates in both behaviors (Zelenin, 2011). Thus heterogeneity of function within cell populations and shared usage of command cells across behavioral routines appear to be a common theme emerging in the control of patterned behaviors in invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Similar control schemes are seen in the lamprey (Buchanan and Cohen, 1982; McClellan and Grillner, 1984; Deliagina et al, 2002). Some reticulospinal neurons, for example, are dedicated to forward or backward locomotion (Zelenin, 2005), although the majority participates in both behaviors (Zelenin, 2011). Thus heterogeneity of function within cell populations and shared usage of command cells across behavioral routines appear to be a common theme emerging in the control of patterned behaviors in invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that during simple, unobstructed locomotion, this modulation is caused by signals coming from the spinal mechanisms generating stepping movements of individual limbs (limb controllers), and different combinations of limb controllers can affect an individual motor cortex neuron and contribute to its modulation (Zelenin et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Activity of motor cortex neurons during backward locomotion. J Neurophysiol 105: 2698-2714, 2011. First published March 23, 2011doi:10.1152/jn.00120.2011 and backward walking (BW) are two important forms of locomotion in quadrupeds.…”
mentioning
confidence: 99%
See 2 more Smart Citations